Growth and inequality examined by integrating the Walrasian general equilibrium and neoclassical growth theories - Wei-Bin Zhang (International Journal of Economic Sciences and Applied Research, 2014)
This paper builds a heterogeneous-households growth model of a small open economy with fixed resource (land) by integrating the Walrasian general equilibrium and neoclassical growth theories. The production side consists of two sectors. We use an alternative utility function proposed by Zhang, which enable us to develop a dynamic growth model with genuine heterogeneity. The wealth and income inequality is due to household heterogeneity in preferences and human capital as well as the households' initial wealth. This is different from the standard Ramsey-type heterogeneous-households growth models, for instance, by Turnovsky and Garcia-Penalosa (2008), where agents are heterogeneous only in their initial capital endowment, not in preference or/and human capital. We simulate the model for an economy with three types of households. The system has a unique stable equilibrium point. We also simulate the motion of the national economy and carry out comparative dynamic analysis with regard to changes in the rate of interest, the population, the propensity to stay at home, and the propensity to save. The comparative dynamic analysis provides some important insights.
Keywords: O31; E31; 330; growth; inequality; capital accumulation; small open economy; wealth and income distribution